Improving Performance of All‐Polymer Solar Cells Through Backbone Engineering of Both Donors and Acceptors. Issue 12 (27th September 2018) - Duan, Chunhui; Li, Zhaojun; Pang, Shuting; Zhu, You‐Liang; Lin, Baojun; Colberts, Fallon J. M.; Leenaers, Pieter J.; Wang, Ergang; Sun, Zhao‐Yan; Ma, Wei; Meskers, Stefan C. J.; Janssen, René A. J.
Abstract : All‐polymer solar cells (APSCs), composed of semiconducting donor and acceptor polymers, have attracted considerable attention due to their unique advantages compared to polymer‐fullerene‐based devices in terms of enhanced light absorption and morphological stability. To improve the performance of APSCs, the morphology of the active layer must be optimized. By employing a random copolymerization strategy to control the regularity of the backbone of the donor polymers (PTAZ‐TPD x ) and acceptor polymers (PNDI‐T x ) the morphology can be systematically optimized by tuning the polymer packing and crystallinity. To minimize effects of molecular weight, both donor and acceptor polymers have number‐average molecular weights in narrow ranges. Experimental and coarse‐grained modeling results disclose that systematic backbone engineering greatly affects the polymer crystallinity and ultimately the phase separation and morphology of the all‐polymer blends. Decreasing the backbone regularity of either the donor or the acceptor polymer reduces the local crystallinity of the individual phase in blend films, affording reduced short‐circuit current densities and fill factors. This two‐dimensional crystallinity optimization strategy locates a PCE maximum at highest crystallinity for both donor and acceptor polymers. Overall, this study demonstrates that proper control of both donor and acceptor polymer crystallinity simultaneously is essential to optimize APSC performance. Abstract : The device performance of all‐polymer solar cells is systematically optimized by modulating the crystallinity of the donor and acceptor polymers via controlling the regularity of their main chains. Experimental and coarse‐grained modeling results reveal that reducing the backbone regularity of either donor or acceptor results in poorer device performance due to a reduced crystallinity and contracted domain size in blends.